Effect of temperature on welding of metallic nanowires investigated using molecular dynamics simulations. Issue 2 (22nd January 2016) - Wu, Cheng-Da; Fang, Te-Hua; Wu, Chung-Chin
Abstract : The mechanism of welding of Au–Au, Ag–Ag and Au–Ag nanowires (NWs) with head-to-head contact is studied using molecular dynamics simulations based on the second-moment approximation of the many-body tight-binding potential. The effect of temperature in the range of 300–900 K is investigated. Simulation results show that at the initial welding, an incomplete jointing area forms through the interactions of the van der Waals attractive force, and that the jointing area increases with increasing the extent of contact between the two NWs during the welding process and temperature. Few defects form along the (1 1 1) close-packed plane during the welding process because the acting stress is quite low. Among the three NW pairs, the Au–Au NWs have the best cold-welding quality, whereas the Au–Ag NWs have the worst cold-welding quality due to the welding of different materials. With an increase in temperature, the weld stress and the mechanical strength of the NWs significantly decrease, and the number of disordered structures increases. The welding fails when the temperature exceeds the molten temperature of the NWs.